História de uma Crise: a crítica de cinema na esfera pública - CARREIRO, Rodrigo (Contemporanea : Revista de Comunicação e Cultura, 2009)
Because of the conditions of production and circulation of information, brought by technological evolution of the Internet, the virtual version of the concept of public sphere starts to evolve in concrete ways. This essay pretends to analyze this phenomenon, taking as object contemporary movie criticism which has found its way into blogs, websites and on-line magazines. The starting point observes that contemporary criticism passes by a process of adjustment, with less space in classical media (newspapers, magazines, radios and TB stations) and more room in cyberspace, where it can bring back part of the original social function, which is cultural resistance. This changing of territory also brings up a negative aspect, which is the homogeneity of the critical discourses, partly because of the free and fast circulation of information published on the Web.